The Impact of Social Media Use Intensity on Adolescent Mental Health: The Mediating Role of Anxiety and Self-Esteem - Tianyi Gao; Qing Zhong; Zhuzi Zhou (Scientific Journal Of Humanities and Social Sciences, 2026)
As more and more social media platforms are emerging, there has been an increased awareness of how they can affect the mental health of youth. We examine the effects of SMUI on mental health (specifically on the constructs of anxiety and self-esteem) among adolescents as possible mediators. A mediation model is developed based on a survey sample of 1, 286 middle and high school students (12-18 years of age) to explore the transmission pathways. The empirical results show that there is a significant relationship between increased SMUI and decreased mental health outcomes. The relationship between SMUI and mental health is partly mediated by anxiety and there is also an important part mediation by self-esteem. Based on the results of the heterogeneity analysis, it can be seen that the mediating role of anxiety is greater for female adolescents, while for the age group 15-18 years, the mediating role of self-esteem is greater. Results from alternative measurement instruments and subgroup analysis are found to be stable. Empirical evidence to understand how social media use is psychologically linked to adolescent well-being is provided and implications for intervention strategies are discussed.